Characterization of saba banana (Musa balbisiana) peel burger patty. - Jagunap, Ihra Divine Jinon
The study focused on the formulation and characterization of Saba banana peel burger patty. Three different formulations with varying amounts of Saba banana peel to texturized vegetable (TVP) ratio (100%, 75%, and 50%) were subjected to rank test for preference to determine the most preferred formulation. Total ranks of the Saba banana peel burger patties from the three formulations showed no significant differences (Kruskall Wallis Test, α = 0.05) but the product with a 100:0 Saba banana peel to TVP ratio was considered as the most preferred formulation because it had the lowest total rank. The Saba banana peel burger patty from this formulation was subjected to further analysis which included pH determination and proximate analysis. The most preferred formulation of the Saba banana peel burger patty a mean pH value of 6.86. It had a moisture content of 56.4%, 13.28% crude fat, 0.78% crude fiber, 1.80% protein, 5.08% ash content, and 22.65% carbohydrates. The Saba banana peel burger patty from the most preferred formulation was characterized through descriptive sensory evaluation as brown to light brown in outer color, with slight to not perceptible banana peel odor, slight to not perceptible banana peel flavor, moderately tender and firm texture, and juicy to slight juicy. Out of eighty (80) respondents, 87% evaluated the product as ?like very much? and 13% rated it as ?like moderately.? None of the consumers disliked the product. Thus, the product has market potential and is a good substitute for beef burger patties.